Pengaruh Kepemilikan Manajerial, Kebijakan Utang dan Ukuran Perusahaan Terhadap Manajemen Laba - Arthawan, Putu Teddy; Wirasedana, Wayan Pradnyantha (E-Jurnal Akuntansi, 2018)
This study aims to investigate empirically evidence of the effect of managerial ownership, debt policy and firm size on earnings management. Managerial ownership, debt policy and firm size as independent variables tested in this study while earnings management as a dependent variable. The sample in this study are 15 non-financial services companies listed in Indonesia Stock Exchange 2012-2015. To measure earnings management by using discretionary accruals calculated from modified jones model, while managerial ownership is measured by the proportion of stock ownership, debt policy is measured by debt to equity ratio (DER) and firm size is measured by total assets. The results of this study indicate that managerial ownership, debt policy and firm size have a negative and significant impact on earnings management. Based on the results of determination coefficient test (R2), the effect of managerial ownership, debt policy, and firm size influence 30.6 percent and the rest of 69.4 percent influenced by other variables not included in the study. Keywords : Profit Management, Managerial Ownership, Debt Policy, Company Size